2007
DOI: 10.1038/sj.jhh.1002238
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in subjects with white-coat hypertension: impact on left ventricular structure and function

Abstract: Some reports have suggested that white-coat hypertension (WCH) is associated with some features of the metabolic syndrome (MetS). These metabolic disturbances, instead of WCH per se, may potentially explain the greater extent of end-organ damage sometimes observed in WCH subjects (WCHs) when compared to normotensive individuals (NTs). The aim of the present cross-sectional study was to compare left ventricular (LV) structure and function in three groups of subjects: WCHs with MetS, WCHs without MetS and NTs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The missing association of white-coat hypertension with inappropriate levels of the studied adipokines, even after adjustment for confounders including postural reactions to standing, suggests that these molecular signals might not be implicated on the association of isolated clinic hypertension with target organ damage. 42 Further clinical studies are needed to confirm the possible prognostic value of Res and Adp on BP levels, including the determination of the physiologically relevant concentrations of the measures associated with adverse clinical BP phenotypes. On the presumption that both of the measures are associated with the out-of-clinic clinical BP phenotypes, and that drugs blocking the renin-angiotensin system proved to increase Adp levels, it should be tested whether these drugs are equally effective for reducing Res levels.…”
Section: Discussionmentioning
confidence: 99%
“…The missing association of white-coat hypertension with inappropriate levels of the studied adipokines, even after adjustment for confounders including postural reactions to standing, suggests that these molecular signals might not be implicated on the association of isolated clinic hypertension with target organ damage. 42 Further clinical studies are needed to confirm the possible prognostic value of Res and Adp on BP levels, including the determination of the physiologically relevant concentrations of the measures associated with adverse clinical BP phenotypes. On the presumption that both of the measures are associated with the out-of-clinic clinical BP phenotypes, and that drugs blocking the renin-angiotensin system proved to increase Adp levels, it should be tested whether these drugs are equally effective for reducing Res levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that MetS is associated with elevated LVM, 6,7,12,[16][17][18][19][20][21][22][23][24][25] but the potential influence of gender on MetS-related LVH is controversial. 6,17,24,25 In a study conducted on 618 hypertensive patients a remarkable sex difference in the association between MetS and LVH was found; indeed, in that study, MetS was a strong determinant of LVM in women beyond the influence of body size and haemodynamic variables, whereas the relation was weaker and fully explained by the effect of confounding factors in men.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Subjects with left ventricular mass (LVM) in the upper normal range already have increased risk for CV events. 15 MetS has been associated with an increased LVM in recent reports conducted in hypertensive patients and in general population, 6,7,12,[16][17][18][19][20][21][22][23][24][25] independently of various confounding factors, such as BP values and age. However, only in a few of these studies the impact of MetS on LVM was separately analysed by gender, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between MS and left ventricular mass was not affected by gender. An additional study by Mule et al 10 showed that MS may have a deleterious influence on left ventricular structure and function even in white coat hypertension.…”
mentioning
confidence: 99%
“…Earlier studies have shown that hypertensive patients with MS are more susceptible to develop LVH than those without MS. [7][8][9][10] Mule et al 9 showed in 475 non-diabetic subjects with mild-to-moderate essential hypertension, of whom 40% had MS, that left ventricular mass was significantly higher in those with MS than in those without it. The relationship between MS and left ventricular mass was not affected by gender.…”
mentioning
confidence: 99%